Analysis of Capacity Building of Small, Micro and Medium Farming Enterprises (SMMEs) In South Africa - Victor Mmbengwa; Xiaoshun Qin (Current Topics on Business, Economics and Finance Vol. 4, 2023)
In this article, it was found that capacity needs for farming SMMEs can bereliably predictedby using the key success factors. In predicting the performance of these enterprises, the use of both key success factors and SSWFOT analysis seems to provide reliable and accurate estimates of the capacity requisites for farming SMMEs. Small, micro, and medium-sized enterprises (SMMEs) have been identified as a crucial strategic priority for South African agrarian development, job creation, and food security. According to recent studies, these SMMEs are unable to function as legal business entities in South Africa. The data was collected during focus sessions and workshops. The survey instrument in the study formed by self-completion questionnaire comprising of 35 closed–ended items was employed these questionnaires were administered to a sample of 105 farming SMMEs across the six (n=6) provinces of South Africa. According to the findings, key success indicators like sustainable markets, input supply, production, increased income/cash flow, and business operations must be developed in order for small and micro enterprises to be financially viable. Additionally, it was discovered that medium-sized businesses have better capacity, and that in order to strengthen their capacity, the right intervention may be needed.